(untitled) (Research, Society and Development, 2020)
Hospitality in tourist destinations plays a fundamental role in promoting tourism. Assuming that the tourist must leave the destination visited with a successful experience. In line with this assumption, we seek to understand how hospitality contributes to the quality of services to the detriment of a positive generation of the travel experience. This article aims to analyze the scientific production of thematic hospitality in tourist destinations. As a methodology, studies were selected from the scientific database SCOPUS, using keywords that covered this theme: “hospitality in the tourist destination and experience”. From the analysis of these articles, it is concluded that hospitality, in its most varied aspects, is intrinsic in the tourist activity, being in the reception and / or in the provision of services, playing an essential role in generating a positive experience for tourists on their trip. It was identified as a gap in this study, in this specific database, the lack of theoretical depth of these dimensions of hospitality, as well as the absence of models of hospitality with applicability in the tourist destination. However, if you have as a suggestion for future studies, investigations that measure hospitality in its most varied aspects and that present validated and applicable theoretical / practical models for the tourist activity as a whole.